PENYULUHAN HUKUM PERJANJIAN DALAM PENINGKATAN BISNIS DI BALAI PEMASYARAKATAN KELAS II BUKITTINGGI - Fauziah , Hanifa Nur; Adriaman , Mahlil (ASOSIASI IDEBAHASA KEPRI, 2024)
This community service is based on the importance for people to know their rights in carrying out transactional relationships in their daily lives. As a guide, the public needs to know the basics of contract law that applies in Indonesia so that they can understand and implement the law that applies in Indonesia. Correctional Institutions (abbreviated as LP or LAPAS) are places for providing guidance to prisoners and correctional students in Indonesia. This means that Correctional Institutions are well prepared so that in the future, after the prisoner's sentence is over, they will return to the community with certain skills that have been trained at the Institution. Correctional. After the legal education activities carried out, we are of the opinion that material regarding increasing public understanding of the legal basis of agreements and the validity of agreements containing exoneration clauses needs to be further improved. Because from the discussions and questions and answers during the counseling, many questions and answers took place between the community and the material givers regarding various issues regarding the validity of the agreements they made in general, and more specifically regarding the legal position of agreements.